Composition, diversity and structure of vascular epiphytes in two contrasting Central Amazonian fl oodplain ecosystems - (:unkn) unknown (Museu Paraense Emilio Goeldi, 2017)
Research focusing on assemblages of vascular epiphytes in the Amazon are scarce. Th is is especially true for Amazonian fl oodplain forests, for which only two previous studies have been published. We compared composition, richness and structure of epiphyte assemblages in white-water and black-water fl oodplains (várzea and igapó) in Central Amazonia in order to close knowledge gaps concerning the distribution and richness of epiphytes. We established sixteen 25x25 m plots in each forest type, and counted and identifi ed all species of vascular epiphytes occurring on trees with a diameter at breast height (DBH) ≥10 cm. We observed a clear distinction in epiphytic species composition (r2=0.83, p=0.001) and diversity (t=3.24, P=0.003) between the two environments, with 61.5 % of species being restricted to várzea, 22.9 % restricted to igapó and only 15.6 % common to both ecosystems. Th e fl oodplains were also structurally diff erent for the most abundant species and those with the highest Epiphytic Importance Value (IVe). Th e diversity of trees did not infl uence the epiphyte diversity in either ecosystem. Th e forests were found to diff er in the composition, diversity and structure of their epiphytic assemblages, which must be taken into account when designing conservation action plans for these ecosystems and for their vascular epiphytes.
Composição, diversidade e estrutura de epífitos vasculares em dois ecossistemas contrastantes da Amazônia Central
Keywords: Amazon; biodiversity; fl oodplains; igapó forests; várzea forests; CNPQ::CIENCIAS BIOLOGICAS::BOTANICA